Репрезентація українсько-єврейських відносин у творах Шолом-Алейхема та Б.Грінченка - Левітас, Ф.; Ковбасенко, Ю.; Салата, О. (Український історичний журнал, 2020)
Аналізуються події, які свідчать про спільну історію українського та єврейського народів. Автори показують, що українсько-єврейські відносини займають важливе місце у розвідках Шолом-Алейхема й Б.Грінченка. Репрезентацію умов співіснування, взаємодії обох народів здійснюють не лише професійні історики. Це питання має міждисциплінарний характер, тому у процесі його дослідження
вивчаються як історичні, так і літературні джерела. Мета статті полягає в намаганні показати позитивний бік українсько-єврейських відносин у контексті спільної історії ХХ ст., відображених у літературних
творах обох письменників. Завдання дослідження: розкрити політику російського самодержавства,
спрямовану на створення суспільно-політичних умов, за яких між українським та єврейським народами
виникали непорозуміння й конфлікти; проаналізувати твори Шолом-Алейхема, Б.Грінченка, що висвітлювали українсько-єврейські відносини на початку ХХ ст.; виявити справжніх організаторів єврейських
погромів через літературні джерела тих буремних часів. В основі методології лежить використання загальнонаукових і спеціальних історичних методів, у тому числі діалектичного, аналізу й синтезу. Наукова
новизна. Досліджується бачення подій початку ХХ ст. єврейським та українським народами, зокрема подібності, а також принципові розбіжності. Висновки. Проаналізовано низку праць українських письменників і публіцистів, адже літературні твори можуть слугувати джерелами недеформованої та достовірної
історичної інформації. Представлено авторські концепції Шолом-Алейхема й Б.Грінченка, на думку яких
єврейські погроми початку ХХ ст. інспірував уряд Російської імперії, а у стосунках українців з євреями
було набагато більше позитиву, ніж неґативу. Розкрито характер боротьби українського народу за національне та соціальне визволення, усупереч антисемітській політиці самодержавства. Events that testify to history of the Ukrainian and Jewish people are analysed. Authors show
that the Ukrainian Jewish relations occupy an important place in researches of modern historians.
Researches of terms of coexistence and cooperation of both people carry out not only professional
historians. This question carries interdisciplinary character, that is why in the process of his research
studied as historical also literary sources. The purpose of the research: to show the positive side of
Ukrainian-Jewish relations in the context of the common history of the twentieth century, reflected in
the literary works of Sholem Aleichem and B.Hrinchenko. To show the policy of autocracy, aimed at
creating socio-political conditions in which between the two peoples there were misunderstandings
and clashes; to analyze the works of Sholem Aleichem and B.Hrinchenko, which cover Ukrainian-
Jewish relations at the beginning of the twentieth century; to find out the true organizers of Jewish
pogroms because of the literary works of those turbulent events. The research methodology. In
modern historiography, the issue of Ukrainian-Jewish relations is extremely relevant. The study of
Ukrainian-Jewish relations requires the integration of methods and approaches of other scientific
disciplines since it should be comprehensive and systematic. The methodology is based on the use
of a variety of general scientific and special methods: the dialectical method, according to which
the relations and the common life of Ukrainians and Jews are considered in their development,
interconnection and interaction; methods of analysis and synthesis, by which the role and place of both
peoples are defined, their rights are in the legal system of Ukraine. The scientific novelty. Important in
this context is the study of the vision of the events of the early twentieth century by the Jewish people
and Ukrainians. In what it was similar, and in what were the fundamental differences. The article shows
the vision of S.Yefremov, B.Hrinchenko, M.Hrushevskyi, V.Vynnychenko and other well-known figures
of 1920-ies. Conclusions. A number of works by Ukrainian writers and publicists have been analyzed,
which showed: literary works can serve as sources of undeformed and reliable historical information.
The author’s conceptions of Sholem Aleichem and B.Hrinchenko are presented. According to them,
the Jewish pogroms of the early twentieth century. Were inspired by the government of the Russian
Empire, and in the relations of Ukrainians with Jews there was much more positive than negativity.
Shown the character of the struggle of the Ukrainian people for national and social liberation, in spite
of the anti-Semitic policy of autocracy, is revealed. The authors urge that now it is necessary to focus
the attention of our society on the generally friendly, tolerant nature of the Ukrainian-Jewish relations
that have been developing in Ukraine for many centuries.